Balancing Demands and Resources: The Role of Psychological Resilience in Driving Employee Engagement - Syarifuddin; Dian Indriani; Junaidin (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study explores the relationships among job demands, job resources, burnout, psychological capital, and work engagement in a rice milling factory. Using a quantitative approach, data were collected from 102 employees and analyzed with structural equation modeling. The findings reveal that job demands significantly increase burnout, while job resources reduce burnout and directly enhance work engagement. Burnout negatively impacts work engagement and mediates the effects of job demands and resources. Psychological capital moderates the relationship between job demands and burnout and between job resources and burnout, emphasizing its role in reducing stress and improving resilience. Additionally, psychological capital has a direct positive effect on work engagement. These results underscore the importance of managing job demands, optimizing resources, and fostering psychological capital to reduce burnout and enhance engagement. Practical recommendations include creating supportive environments, providing resilience training, and implementing effective workload management strategies to enhance employee well-being and productivity